أثر استخدام اسلوب الاكتشاف الموجه على تعلم مهارتين أساسيتين في السباحة لدى الأطفال المبتدئين - محمود, بلال; قاسم, سامح; سعود, ندى (Latakia University Journal -Medical Sciences Series, 2018)
This study aims to identify the effect of the guided discovery style on learning the two swimming basic skills (breathing and underwater diving ) on beginner children of ages 4-6 years. The experimental method is used on a sample consisted of (30) children and divided into two equal groups, controlling group consisted of (15) children applied the traditional program and experimental group consisted of (15) children applied a program with guided discovery style to learn the skills (breathing and diving under the water with eyes open). Each group learned in a 90-minutes session one time per week for period of (6) weeks. The results of the study shows a positive impact of the guided discovery style on learning the skills (breathing and diving under the water with eyes open) in swimming on beginner children of ages(4-6) years, and recommended to use the guided discovery style to learn the basic skills in swimming for young children and other ages (especially on learning skills of((breathing (inspiration - exhalation) - underwater diving with open eyes)) and the basic skills of various sports for children. هدفت هذه الدراسة إلى التعرف على أثر اسلوب الاكتشاف الموجه على تعلم مهارتي التنفس والغوص تحت الماء مع فتح العينين لدى الأطفال المبتدئين بأعمار من (4-6) سنوات، وتم استخدام المنهج التجريبي بأسلوب المجموعتين (ضابطة وتجريبية) على عينة مكونة من (30) طفل تم تقسيمهم الى مجموعتين متساويتين, مجموعة ضابطة وعددهم (15) طفل طبق عليهم البرنامج التقليدي ومجموعة تجريبية وعددهم (15) طفل طبق عليهم برنامج تعلم مهارتي ( التنفس والغوص تحت الماء مع فتح العينين) بالسباحة بأسلوب الاكتشاف الموجه وبواقع وحدة تدريسية في الأسبوع الواحد بزمن (90) دقيقة ولمدة (٦) أسابيع. وأظهرت نتائج الدراسة أن أسلوب التدريس بالاكتشاف الموجه له اثر ايجابي على تعلم مهارتي التنفس والغوص تحت الماء مع فتح العينين في السباحة لدى الأطفال المبتدئين بأعمار (4-6) سنوات، ومن توصيات الدراسة استخدام اسلوب الاكتشاف الموجه في تعلم المهارات الاساسية في السباحة للأطفال المبتدئين وللفئات العمرية الأخرى وخاصة في تعلم مهاراتي ((التنفس (شهيق – زفير) - الغوص تحت الماء مع فتح العينين)) والمهارات الأساسية للألعاب الرياضية المختلفة للأطفال.